Synergistically Optimizing Electrical and Thermal Transport Properties of BiCuSeO via a Dual‐Doping Approach. Issue 9 (22nd February 2016) - Liu, Yong; Zhao, Li‐Dong; Zhu, Yingcai; Liu, Yaochun; Li, Fu; Yu, Meijuan; Liu, Da‐Bo; Xu, Wei; Lin, Yuan‐Hua; Nan, Ce‐Wen
Abstract : The layered oxyselenide BiCuSeO system is known as one of the high‐performance thermoelectric materials with intrinsically low thermal conductivity. By employing atomic, nano‐ to mesoscale structural optimizations, low thermal conductivity coupled with enhanced electrical transport properties can be readily achieved. Upon partial substitution of Bi 3+ by Ca 2+ and Pb 2+, the thermal conductivity can be reduced to as low as 0.5 W m −1 K −1 at 873 K through dual‐atomic point‐defect scattering, while a high power factor of ≈1 × 10 −3 W cm −1 K −2 is realized over a broad temperature range from 300 to 873 K. The synergistically optimized power factor and intrinsically low thermal conductivity result in a high ZT value of ≈1.5 at 873 K for Bi0.88 Ca0.06 Pb0.06 CuSeO, a promising candidate for high‐temperature thermoelectric applications. It is envisioned that the all‐scale structural optimization is critical for optimizing the thermoelectricity of quaternary compounds. Abstract : A record‐high ZT value, the figure of merit, of ≈1.5 at 873 K in BiCuSeO is achieved through a Pb and Ca dual‐doping approach. Synergistically, the power factor is optimized by electrical structure tuning with Pb dopants, and the thermal conductivity is reduced by phonon scattering at CaO2 nanoclusters.